Islamisasi Psikologi - Ahmad Abdul Khozim (Lembaga Penerbitan dan Publikasi Ilmiah IAI Bunga Bangsa Cirebon, 2020)
The birth of a theory / science cannot be separated from what is called philosophy. Because in the realm of efistemology, philosophy is a person's frame of mind (read: scientists) in producing theories / science itself. Thus, the birth of a theory developed in a scientific discipline - its ontology, efistemology and axiology - is strongly influenced by the flow of philosophy itself. The philosophy of positivity which relies more on scientific aspects (logic, empiric and rational) and sees humans as only as a material being, of course it will give birth to a different view of humans compared to the theory developed on top of Islamic philosophy. The birth of this distinction is due to a different perspective on humans themselves as a formal object of psychological study. The development of Western psychology (which is built on scientific and secular-materialist foundations) has indeed given meaning to the development of the world of Islamic education, especially for analyzing educational problems related to human psychological aspects. However, the presence of Western psychology is not something that must be fully accepted without analyzing and filtering, but it needs to be reviewed, especially in its efistemology, so that the theories that are born from western psychology are truly relevant to the Islamic perspective. Abstrak Lahirnya sebuah teori/ keilmuan tidak bisa dipisahkan dari apa yang disebut dengan filsafat. Sebab dalam ranah efistemologi, filsafat merupakan kerangka berpikir seseorang (dibaca:ilmuan) dalam memproduksi teori-teori/ keilmuan itu sendiri. Dengan demikian, kelahiran sebuah teori yang dikembangkan dalam suatu disiplin ilmu – ontologinya, efistemologinya dan axiologinya-,sangat dipengaruhi oleh aliran Filsafat itu sendiri.Filsafat positifisme yang lebih menyandarkan pemikirannya pada aspek-aspek ilmiah (logika, empiric dan rasional) serta melihat manusia hanya sebagai makhluk material, tentu akan melahirkan pandangan yang berbeda terhadap manusia dibanding dengan teori dikembangkan di atas filsafat islam. Lahirnya distingsi ini karena cara pandang yang berbeda terhadap manusia itu sendiri sebagai objek formal kajian psikologi. Perkembangan psikologi Barat (yang dibangun di atas landasan ilmiah dan materialis-sekuler), memang telah memberikan arti terhadap perkembangan dunia pendidikan islam, terutama untuk menganalisis persoalan-persoalan pendidikan yang terkait dengan aspek psikologis manusia. Namun demikian, kehadiran psikologi Barat tersebut, bukanlah sesuatu yang mesti diterima sepenuhnya tanpa menganalisis dan memfilter.melainkan perlu di telaah kembali terutama dalam aspek efistemologinya, supaya toeri-teori yang dilahirkan dari psikologi barat betul-betul relevan dengan perspektif islam.